The Effect of Fiscal Policy Uncertainty on the Probability of Future Recession in the U.S.and Canada - Li, Jiaxiong (Université d'Ottawa | University of Ottawa, 2013)
This paper studies the effect of fiscal policy uncertainty on the probability of future recession using the U.S. and Canadian data. The study uses the economic policy uncertainty index developed by Baker, Bloom, and Davis (2011) as a proxy for fiscal policy uncertainty and the recession indices constructed by the Organization for Economic Co-operation and Development (OECD). The analysis starts with computing the dynamic correlations between the uncertainty index and the recession index for each country and for each of the four quarters ahead. Then a probit regression model is employed to examine the predictive power of the uncertainty index for the probability future recession. The results show that the overall effect of fiscal policy uncertainty on the probability of future recession is ambiguous in both the U.S. and Canada. However, after controlling for the interest rate, the effect of policy uncertainty is amplified, suggesting that the monetary policy may play an important role in smoothing the business cycle. Lastly, the additional effect of policy uncertainty is diminished and become insignificant when all potential leading indicators are included in the probit regression model.